Pemanfaatan Vitamin, Pemeriksaan Kesehatan Serta Swamedikasi di Kelurahan Lirang Kecamatan Lembe Utara - Rahmat Ismail; Ahlan Sangkal (PT. ALHAFI BERKAH INDONESIA, 2023)
One of the efforts that can be made to improve public health is by providing self-medication training and detecting health early. The understanding of the Lirang Village community regarding the use of medicines around residents' homes to be used as medicine as well as giving vitamins and early examinations is still lacking and not optimal in utilizing traditional plants. Training and counseling are carried out at the lirang sub-district hall of the Lirang Sub-District Government, the Lirang Sub-District community, and local organizational cadres. The activity begins with checking blood pressure, blood sugar, cholesterol and uric acid followed by counseling on how to choose vitamins and practice training on making herbal medicines. The activity was carried out well and received an enthusiastic response from the Lirang Village community. Kelurahan Lirang is very accepting and open if there is a similar training that will be held in the future.